PENGARUH MEDIA MAPS HALANG RINTANG TERHADAP MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN TEMATIK TEMA 7 SUBTEMA 1 KELAS 1 SEMESTER II SDN 01 GROBOGAN KECAMATAN GROBOGAN KABUPATEN GROBOGAN, TAHUN AJARAN 2017/2018 - Sari, Puspa Eva Ratna Kumala; Purnomo, Joko; Mushafanah, Qoriati (KALAM CENDEKIA PGSD KEBUMEN, 2018)
AbstractThis type of research is quantitative research, the design used in the research is Quasi Experimental with nonquivalent form Control Group Design. The population of this research is all students of class I SDN 01 Grobogan Lesson Year 2017/2018. Samples taken are 25 students. Data from this research is obtained through observation, interview, test, questionnaire and documentation. The result of the research analysis showed that the classical percentage of UTS (50%) while the classical percentage posttest (79%), based on the correlation test results obtained rcount> rtable or 0.396> 0.361 so H0 rejected and Ha accepted. It can be concluded that there is a correlation between students' perceptions with Halang Rintang Maps media on the motivation of first grade students of elementary school 01 Grobogan and its influence is 97% t test results obtained thitung = 4,69. Furthermore tcount is compared with ttable = 0,063 with t1-1 / 2 ? at significant level ? = 5%, so obtained-t table <t count <ttabel that is 0,063 <4,69 <0,063. Thus H0 is rejected and Ha accepted. It can be concluded that there are differences in learning outcomes between students who have high motivation with low motivation students on thematic learning Class I SD 01 Grobogan. Keywords: Game Methods, Media Maps Obstacle, Learning MotivationAbstrak Jenis penelitian ini adalah Quasi Eksperimental dengan bentuk nonquivalent Control Group Design. Populasi penelitian ini adalah seluruh siswa kelas I SDN 01 Grobogan Tahun Pelajaran 2017/2018. Sampel yang diambil adalah 25 siswa. Data dari penelitian ini diperoleh melalui observasi, wawancara, tes, angket dan dokumentasi. Hasil analisis penelitian menunjukan bahwa presentase klasikal UTS (50%) Sedangkan pada presentase klasikal posttest (79%), berdasarkan hasil uji korelasi diperoleh rhitung > rtabel atau 0,396 > 0,361 sehingga H0 ditolak dan Ha diterima. Dapat disimpulkan bahwa ada korelasi antara persepsi siswa dengan media Maps Halang Rintang terhadap motivasi belajar siswa kelas I SD Negeri 01 Grobogan dan pengaruhnya sebesar 97% Hasil uji t diperoleh thitung = 4,69. Selanjutnya thitung tersebut dibandingkan dengan ttabel = 0,063 dengan t1-1/2